Inclusão do farelo da amêndoa da castanha de caju na ração de postura para codornas - Soares, Marcelo Borges (2005)
This study was undertaken to evaluate bird performance and egg characteristics of japanese quails fed diets containing 0; 4; 8; 12; 16 and 20% of cashew nut meal (CNM). A total of 270 japanese quails with 17 weeks of age were weighed and distributed in a completely randomized design with six treatments and nine replicates of five birds in each experimental unit. Diets were isonutrient and during nine weeks of experimental period birds received feed and water ad libitum along with 16 hours lighting. Feed intake was not affected by the inclusion of CNM. Regression analysis, excluding diet with 0% CNM, showed that egg production, egg weight, egg mass and feed conversion decreased linearly as dietary CNM levels increased in diets. Percentages of albumen and yolk as well as yolk color, however, showed a quadratic effect as dietary CNM levels increased.Albumen percentage and yolk color increased and yolk percentage decreased as CNM increased up to the level of 9% of the diet. Comparing to the control diet only treatment with 20% CNM produced significantly (P<0.05) lower egg production, egg weight, egg mass, yolk color and bird feed conversion. In conclusion CNM can be included in japanese quail diets in levels up to 16%.